PERSONNEL PROVISION OF TECHNOLOGICAL LEADERSHIP: GOOD PRACTICE EXAMPLES OF CHINA AND REPUBLIC OF KOREA - A. V. Ozornin; F. A. Kurakov (Ekonomika Nauki)
There was evaluated an amount of students fromChinaandRepublicofKorea, that received education inUSAuniversities in the period between 2000 and 2014 years. It was noted that starting from 2008 there has been a gradual growth in the quantity of Chinese students, referred to the best American universities. Analysis of the programs, where most of the students fromChinaandRepublicofKoreawere enrolled into allowed to identify an absolute priority of engineering majors programs. Using the data ofInstituteofInternational Educationit was demonstrated that in the period between 2008–2014 yearsChinainvested 31,88 billion USD to have 1087,5 thousand specialists receive education and training in US universities. There is a hypothesis made, that particularly this body of graduates — carriers of new technology competencies enabledChinabecome a technological leader in a broad range of areas of production technologies. There were analyzed results of realization of the first stage of the «Global Education» project, and demonstrated that selection of the winners is not always linked to technological priorities of Russia and choice of competency centers for obtaining world-class education in series of cases is poorly justified.